Direct reliability: strategies to revolutionize healthcare. - Babyar, Julie (Journal of Public Health: From Theory to Practice (2198-1833), 2020)
Aim: The aim of this article is to understand the current climate of high reliability in healthcare and explore comprehensive approaches to measure future healthcare transformation. Subjects and methods: Literature pertaining to high reliability in industry and healthcare organizations was reviewed, with a focus on publications from 2006–present. Results: Readiness assessments, components, frameworks and comparisons to external industries have been produced in the literature and discussed within healthcare expertise. High reliability in healthcare organizations remains opaque, with varied structures to recommendations, despite continued interest and accreditation focus. Advancing high-reliability science for healthcare has remained elusive. Conclusion: Strategies to revolutionize healthcare utilizing reliability should be considered imperative opportunities. These strategies include conceptualizing high-reliability science for healthcare as holistic, incorporating recommended robust process improvements along all spectra of healthcare, standardizing criteria to constitute a high-reliability organization in healthcare and measuring high reliability qualitatively, with the understanding that avoided catastrophic failures should be factored, and emphasizing public trust in medicine as a priority for high reliability. Notably, patient satisfaction and patient perception of reliable healthcare must be included at the forefront. By harnessing these strategies, healthcare will move reliability from an indirect cultural philosophy to the direct, revolutionary spotlight. A spotlight on reliability is positive, commendable and important to honor.